Pengaruh Penggunaan Gadget Terhadap Perkembangan Kompetensi Sosial Pada Anak Usia Dini - Dwi Anisak Nurul Fitri (Jurnal El-Audi, 2024)
Technological developments in the era of the Industrial Revolution 4.0, and some countries are even moving towards the Industrial Revolution 5.0, are a crucial aspect of human life. Gadgets are a product of the increasingly advanced and rapid development of technology and communication. The influence of gadgets is like two sides of a coin, capable of both positive and negative impacts, particularly on the social development of early childhood. The purpose of this study is to describe the impact of gadget use on early childhood social development. This study employed a qualitative approach, using a case study method, with three children aged 3-5 years and their parents. Data collection techniques included interviews and observations. Interviews were conducted with the mothers of the respondents through a discussion and Q&A process. The researchers conducted observations by directly observing the respondents in the field. Data analysis was conducted using a Grounded Theory approach. The results of this study explain that the impact of gadget use on early childhood is like two sides of a coin, where on the one hand it has a positive impact but on the other hand it has a negative impact. This depends on how parents control/supervise their children's use of gadgets.